Utilitarianism in Halal Tourism Development in Indonesia - Santoso, Lukman; Wahid, Soleh Hasan (Fakultas Syariah UINSI Samarinda, 2023)
Halal tourism is one of the fastest-growing areas in the world economy. As a Muslim-majority country, Indonesia has the potential to promote halal tourism. However, there are still many problems in the development of halal tourism to realize sustainable benefits and the welfare of the people. This study aims to explore the development of halal tourism in Indonesia from a helpful philosophical perspective. By using a qualitative-interpretative approach, this study employed a library research method. This study provides findings that the development of halal tourism in Indonesia has not given the maximum benefit and welfare impact. Therefore, in the future, in formulating tourism development policies, it is essential to prioritize integrative and responsive aspects by involving all stakeholders and aligning them with the sustainable national development framework. The contribution of this study seeks to present regulatory formulations that have a positive impact on many people and rely on rule utilitarianism. Thus, it will give birth to a halal tourism policy that is inclusive, humane, and contextual to national and global dynamics.